Comprehensive 2D-carrier profiling of low-doping region by high-sensitivity scanning spreading resistance microscopy (SSRM) for power device applications. Issue 9 (August 2015) - Zhang, L.; Koike, M.; Ono, M.; Itai, S.; Matsuzawa, K.; Ono, S.; Saito, W.; Yamaguchi, M.; Hayase, Y.; Hara, K.
Abstract: Superjunction (SJ) MOSFETs with low on-resistance and high sustain voltage are widely used as main switching power devices. For the p / n -pillars of SJ-power devices, precise doping at low-doping region below 10 16  cm − 3 concentrations is required, and thus high-sensitivity 2D-carrier profiling of the pillars is indispensable where conventional SCM is insufficient. Previously, we developed the high-vacuum SSRM enabling high-spatial resolution and site-specific 2D-carrier profiling. In this study, we investigated comprehensively the feasibility of applying SSRM to SJ-power devices at low doping below 10 16  cm − 3, with both SJ-diodes and low-doping references. The bias dependence of SSRM was analyzed on SJ-diodes and was compared with T-CAD simulations, and both the p - and the n -pillars demonstrate Schottky-like behavior between the probe and the sample. Consequently, the pn -junction delineation also moved with applied bias. We also performed SSRM on reference-staircase structures with low-doping layers down to 10 14  cm − 3 of p, n and p / n types, and comparison with SIMS and SRP confirmed the high sensitivity of SSRM. The Schottky contact of the probe-sample was found to be pronounced at low-doping region, particularly p -type doped region. Therefore, the bias polarity should be taken into account to obtain correct information at the low-doping region.